Pengaruh Gaya Mengajar Latihan Terhadap Gerak Dasar Pada Servis Bawah Dalam Permainan Bola Voli Peserta Didik Kelas VIII SMP Negeri 3 Tondano - Ika Putri; Edita A.M. Pinangkaan; Eduard E. Kumenap (STIKES Columbia Asia Medan, 2025)
This study aims to test the application of teaching styles in improving the basic underhand serve in volleyball. The method used in this research is the experimental method. The sample used in this study consists of eighth-grade students from SMP Negeri 3 Tondano for the 2024/2025 academic year, totaling 20 samples, divided into two groups: the experimental group with a teaching style training consisting of 10 samples and the control group that did not receive treatment, also consisting of 10 samples. The research was conducted over one month with a frequency of three times a week. The research design used is a